2014
DOI: 10.1371/journal.pone.0092551
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in the Fossil Record: A Cretaceous Fauna with Isopod-Infested Decapod Crustaceans, Infestation Patterns through Time, and a New Ichnotaxon

Abstract: Parasites are common in modern ecosystems and are also known from the fossil record. One of the best preserved and easily recognisable examples of parasitism in the fossil record concerns isopod-induced swellings in the branchial chamber of marine decapod crustaceans. However, very limited quantitative data on the variability of infestation percentages at the species, genus, and family levels are available. Here we provide this type of data for a mid-Cretaceous (upper Lower Cretaceous, upper Albian) reef setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 85 publications
1
91
1
Order By: Relevance
“…Parasites are ubiquitous and abundant in all ecosystems and in all groups of living forms (e.g. Klompmaker et al 2014).…”
mentioning
confidence: 99%
“…Parasites are ubiquitous and abundant in all ecosystems and in all groups of living forms (e.g. Klompmaker et al 2014).…”
mentioning
confidence: 99%
“…-Bopyriform swellings (as termed by Wienberg Rasmussen et al 2008), which typically occur on the branchial regions, were recently named Kanthyloma crusta by Klompmaker et al (2014). These swellings are known from many Upper Jurassic decapod assemblages (Bachmayer 1948, Houša 1963, Radwański 1972, Wienberg Rasmussen et al 2008, Robins et al 2012, Klompmaker et al 2014.…”
mentioning
confidence: 99%
“…The sample, however, is too small to draw any conclusions regarding the preference for the left or right branchial side for infestation. Based on statistical data from the Albian of Koskobilo, Spain, Klompmaker et al (2014) concluded that there is no statistical preference for either the left or right branchial side for infestation on the assemblage level.…”
mentioning
confidence: 99%
See 2 more Smart Citations